Formalizing in business networks as a tool for industrial policy. Issue 1 (13th March 2017) - Guercini, Simone; Tunisini, Annalisa
Abstract : Purpose: The purpose of this paper is to examine the issue of "formalization" in business networks as an instrument of industrial policy. Formalization in business networks is not a debated topic but it can affect organizational and inter-organizational dynamics considerably. The aim of the paper is to understand if the introduction of a normative tool that enhances formalized networks can be effective to promote network aggregations among SMEs. Second, the aim is to understand if this formalization supports good-working networks, i.e., capable to introduce new products or to enter new markets/customers. Design/methodology/approach: The paper refers to a review of the literature and mainly to an empirical research on formalized network contracts (NCs) that have been conducted in the latest two years. This research has used both secondary data, collected accessing to databases and reports given by institutions and the government, and primary data, collected in specific direct interviews. These interviews have been concerned both institutions such as Chamber of Commerce, Confindustria and the Ministry of Economic Development and the Small Business Association, and 15 cases of NCs in Italy. Findings: The formalization has consequences both internally and externally to the NC. Internally it can act as an element to reduce ambiguity and building elements of "fragile trust, " in the absence of basic elements of "resilient trust" and in the presence of changes in the competitive environment. Externally, the formalization through the NC allows the policy maker to identify more clearly companies' aggregations in order to let them being destination of specific industrial policies. However even if the formalization has in some cases enhanced new networks' creation, in many cases formalization has generated positive results when companies had already experienced networking outside the frame of the NC. Research limitations/implications: Further research on formalization in networks should be developed following the "history" of formalized networks over time in order to understand how much formalization should be used as a long-term tool for industrial policy. Practical implications: The paper can be useful both for companies that want to sign a NC and for the institutions developing industrial policies devoted to support companies' aggregations in the form of NC. Originality/value: The paper presents a new legal tool – the "NC" – introduced in 2009 by the Italian Government to enhance firms' aggregation; second, the paper debates the topic of formalization in networks that is not much debated in literature; and finally, the paper also adopts an industrial economic approach and is among the few attempts to integrate industrial policies and industrial marketing and purchasing thinking.